Support Vector Machine For Forecasting Currency Rates - Dovdon, Gankhuyag (2003)
Neural network (NN), Group Method Data handling(GMDH), Innovative Support Vector Machine (SVM), time series prediction approach's design and implementation are discussed in this research.